Unique pharmacological properties of etrasimod among S1P receptor modulators - Ibragim Gaidarov; H. Kiyomi Komori; Dariusz T. Stepniak; Karin Bruinsma; Huong Dang; Xiaohua Chen; Todd Anthony; Joel Gatlin; Lisa Karimi‐Naser; Anh‐Tuan Ton; Tim Indersmitten; Paul E. Miller; et al. (FEBS Open Bio)
Etrasimod (ADP334) is an oral, once‐daily, selective sphingosine 1‐phosphate (S1P)1,4,5 receptor modulator for the treatment of moderately to severely active ulcerative colitis and in development for the treatment of immune‐mediated inflammatory diseases. Interaction between S1P and its five receptor subtypes (S1P1–S1P5) plays a role in several physiologic systems, including the cardiovascular and immune systems. Since differences in S1PR binding and downstream intracellular signaling could contribute to distinct profiles of drug efficacy and safety, we directly compared the S1P1–5 selectivity profile of etrasimod to three marketed S1PR modulators: fingolimod, ozanimod, and siponimod. Using both heterologous expression systems and human umbilical vein endothelial cells that spontaneously express S1P1, we profiled key S1P1 downstream signaling pathways and found that etrasimod had similar potency to the other tested S1PR modulators in promoting β‐arrestin recruitment and S1P1 internalization. However, etrasimod was notably less potent than other S1PR modulators in assays measuring S1P1‐mediated G protein activation (GTPγS binding and cAMP inhibition). Relatively lower potency of etrasimod in inducing G protein signaling corresponded to significantly diminished activation of human cardiac G protein‐coupled inwardly rectifying potassium channels when compared to ozanimod. Together with pharmacokinetic properties, this pharmacologic profile of etrasimod may contribute to the positive benefit risk profile of etrasimod observed during the phase III ELEVATE UC 52 and ELEVATE UC 12 trials in patients with moderately to severely active ulcerative colitis.